Biotechnology application in the advanced bioeconomy: opportunities and challenges for productive and sustainable development in Costa Rica - Barahona Carmona, Laura (2024)
[Introduction]: The bioeconomy addresses a series of problems in key areas for the Latin American region. As a result, a growing number of countries worldwide have developed bioeconomy policies or strategies, the Costa Rica Strategy beings the first in the region. [Objective]: The aim of this article is to analyze the opportunities and challenges of the advanced bioeconomy, emphasizing the biotechnology sector, to contribute to the Costa Rican productive and sustainable development. [Methodology]: The approach applied is qualitative based on primary and secondary sources, and ongoing reflection and discussion. [Results]: As a result, it is found that despite facing structural barriers and challenges such as market aspects, coordination governance, waste management, availability and use of biological, financial, educational, social resources, among others; the bioeconomy is positioned along with biotechnology as a great opportunity to develop valorization and management of waste, enhance productive processes and value chains with high added value related to research, development and innovation, knowledge, competitiveness, encouraging the generation of employment, new exports and access to more and better markets. [Conclusions]: It is possible to conclude that the aforementioned can be applied in harmony with natural ecosystems and social welfare that can even be replicated in other countries of the region contributing to improve the social, economic and environmental challenges.